PENGEMBANGAN SISTEM INFORMASI TERINTEGRASI UPT BALAI LATIHAN KERJA DINAS TENAGA KERJA DAN TRANSMIGRASI JAWA TIMUR - Benny Lianto; Dhiani Absari; Felix Handani; Bambang Prijambodo; Arizia Aulia Aziiza; Kiky Octavina (Jurnal Bisnis Terapan, 2022)
Abstract Unit Pelaksana Teknis Balai Latihan Kerja (UPT BLK) is a unit providing training services for job seeker underEmployment and Transmigration Services of East Java Province forspecific work areas. 16 Technical Execution Unit (UPT) and Job Training Center (BLK) under Employment and Transmigration Services serves job seekers through 177 training services. Currently, each UPT BLK runs itstraining services business process in a diverse way.The systems running in each UPT BLKs have not been integrated yetbetween other BLKs and Labor and Transmigration Services of East Java. This leads to non-standard services to the job seeker and the inability of UPT BLK and the Employment and Transmigration Services of East Java to share information quickly. This study aims to develop an integrated information system to implement training so that there is uniformity of service delivery for all UPT BLKs in the DisnakertransJatim by one-gate access. The research was developed using the Design Science Research methodology. A web-based integrated system for all UPT BLKs to assist the process of organizing training is chosen as its artifact. The method of focus group discussion, interviews, and observations throughout the application development process. Based on the results of the evaluation, it was found that 95% of respondents were very satisfied in terms of system usability and were greatly helped by the operational side of the system in completing their work.